An Italian consensus on the management of Lennox-Gastaut syndrome. (October 2022) - Riva, Antonella; Coppola, Antonietta; Bonaventura, Carlo Di; Elia, Maurizio; Ferlazzo, Edoardo; Gobbi, Giuseppe; Marini, Carla; Meletti, Stefano; Romeo, Antonino; Santoro, Katia; Verrotti, Alberto; Capovilla, Giuseppe; et al.
Highlights: Lennox-Gastaut syndrome (LGS) has high clinical and aetiological heterogeneity. Consensus between experts helps make practical guidelines for patients' treatment. More drugs should be considered as first-line treatment options for LGS. Abstract: Purpose: Although international guidelines exist, the clinical heterogeneity of Lennox-Gastaut syndrome (LGS) and the increasing availability of new and repurposed drugs (e.g., fenfluramine and cannabidiol) requires a practical guide to patient management in the clinical context. We report the results of a consensus survey among 42 Italian experts in the diagnosis and treatment of LGS. Methods: The consensus procedure followed a modified Delphi approach. Statements were formulated, based on the most recent published evidence and the clinicians' personal experience, then discussed, and agreed upon by the experts through a two-round voting procedure. Approval of a statement was reached with an average score ≥7. Results: Thirteen statements dealing with three main topics (i.e., clinical diagnosis and prognosis, impact on the Quality of Life (QoL), and treatment strategies) were generated. Six statements achieved a level of agreement sufficient for approval on the first voting round. Following the discussion and a few consequent amendments, most of the statements increased their level of agreement and all 13 were approved. Conclusions: Overall, the statements draw a slightly more benign picture of this rare and severe disease, highlighting the possibility of remission - albeit modest -, an apparent trend towards lower mortality, and the availability of several effective drugs, to which greater accessibility would be hoped for. Valproate remains a major therapeutic option in LGS patients although lamotrigine, rufinamide, topiramate, cannabidiol, and clobazam are popular therapeutic options in Italy, allowing for a tailor-made antiseizure therapy.